Evaluation of the Regional Spatial Plan for Settlements in Siak District Based on Flood Prone Area - ANWAR, AZHARIL NAUFAL; Umar, Iswandi (JURNAL BUANA, 2025)
This study aims to determine the RTRW inconsistency index by analyzing the implementation of the Siak District Settlement RTRW, which is known from the comparison between land use and the Siak District RTRW. The land use map is generated from the SAS Planet high-resolution mind, and the settlement spatial plan map is generated from the 2020–2040 RTRW in Siak District. In addition, to find out the Siak District Settlement Spatial Plan based on disaster-prone areas, a flood disaster-prone analysis was carried out using the "weighted and scoring" method, which was then combined with the Siak District Settlement Spatial Plan Map to evaluate the suitability of settlement planning in Siak District, whether to avoid flood-prone areas or not. The results show that 33.0 percent of settlement land use is not in accordance with the regional spatial plan, and 48 percent of settlement planning is not suitable because it is in a very flood-prone area. Therefore, it is necessary for the Siak district government policy to evaluate the RTRW to be more consistent, pay attention to disaster-prone areas, and implement enforcement for spatial violators.